Aflatoxin B1 Occurrence, Detection and Toxicological Effects - Long, Xi-Dai (Biochemistry, 2020)
This book consists of 11 chapters, divided into four parts. The chapters are written by experts in the field of aflatoxins. Select topics are presented here to provide a snapshot of current understanding of the occurrence and metabolism of aflatoxin B1, the contamination, exposure, and detection of aflatoxin B1, and the toxicological effects and detoxification of aflatoxin. The book is intended for students and scientists working in the field of aflatoxins.